Cyclic Heterometallic Interactions formed from a Flexible Tripeptide Complex Showing Effective Antiferromagnetic Spin Coupling. Issue 10 (18th January 2021) - Miyake, Ryosuke; Suganuma, Eri; Kimura, Shun; Mori, Hirotoshi; Okabayashi, Jun; Kusamoto, Tetsuro
Abstract: Developing tunable motifs for heterometallic interactions should be beneficial for fabricating functional materials based on cooperative electronic communications between metal centers. Reported here is the efficient formation of cyclic heterometallic interactions from a complex containing an artificial tripeptide with metal binding sites on its main chain and side chains. X‐ray structural analysis and X‐ray absorption spectroscopy revealed that the cyclic metal–metal arrangements arise from the amide groups connecting four square‐planar Cu II centers and four octahedral Ni II centers in a cyclic manner. UV/Vis spectral studies suggested that this efficient formation was achieved by the selective formation of the square‐planar Cu II centers and a crystallization process. Magnetic measurements using SQUID clarified that the cyclic complex represented the S =2 spin state at low temperatures due to effective antiferromagnetic interactions between the Ni II and Cu II centers. Abstract : A cyclic Cu II ‐Ni II arrangement was efficiently formed using a flexible tripeptide and it exhibits effective antiferromagnetic spin coupling through the tripeptide amide groups.